Mode-locked fiber laser in the C-band region for dual-wavelength ultrashort pulses emission using a carbon nanotube saturable absorber - Lau K.Y.; Ker P.J.; Abas A.F.; Alresheedi M.T.; Mahdi M.A. (OSA - The Optical Society, 2023)
Carbon nanotubes; Erbium; Fiber lasers; Fibers; Locks (fasteners); Saturable absorbers; Ultrashort pulses; Yarn; Dual wavelength; Erbium doped fiber laser; Erbium doped fibers; Mode-locking fiber laser; Modelocking; Net gain; Pulse durations; Ultrashort Laser; Mode-locked fiber lasers